Origin of Microcells in the Human Sarcoma Cell Line HT-1080 - Indulis Buiķis; Līga Harju; Tālivaldis Freivalds (Analytical Cellular Pathology)
The aim of this study was to investigate the development of microcells in the human sarcoma cell line HT‐1080 after interference with thiophosphamidum. We found that damaged interphase macrocells located at the projection of the nucleolus may form one or several microcells. The micronuclei of the microcells intensively incorporate the thymidine analogue 5‐bromo‐2'‐deoxyuridine and strongly express argyrophilic nucleolar organiser region proteins. At an early phase of the development, the micronuclei contain fragmented DNA, but in subsequent phases, the micronuclei accumulate polymeric DNA, simultaneously with an increase in their size. After desintegration of the damaged macrocell, the microcells appear in the intercellular space. The microcells can enter mitosis and they strongly express the lung resistance protein. Electron microscopic observations suggest that coiled bodies are involved in the development of the microcells. Since the observed path of microcell formation differs from apoptotic cell fragmentation into apoptotic bodies, we propose a new term for this microcell development: sporosis. We suggest that self‐renewal of the tumour stem cells is likely based on sporosis.